Factors Influencing the Decision to Choose a Private University in Jakarta - Muhammad Ricky Syahputra Hendri (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
This research aims to analyze the influence of tuition fees, reference groups, facilities, and brand image on the decision to choose a private university in Jakarta. Using a quantitative approach, an online survey was conducted with 100 first-semester students at a private university in Jakarta. The data were analyzed using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach. The results indicate that tuition fees and brand image have a positive and significant influence on the decision to choose a private university. Conversely, reference groups and facilities were not proven to have a direct significant influence. However, brand image was found to have a full mediating role between reference groups and the decision to choose, and a partial mediating role between tuition fees and the decision to choose. This study concludes that prospective students in Jakarta prioritize financial factors and brand reputation over social recommendations and physical facilities when selecting a university.